2014
DOI: 10.1016/j.dci.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegypti ML and Niemann-Pick type C family members are agonists of dengue virus infection

Abstract: Upon exposure to dengue virus, the Aedes aegypti mosquito vector mounts an anti-viral immune defense by activating the Toll, JAK/STAT, and RNAi pathways, thereby limiting infection. While these pathways and several other factors have been identified as dengue virus antagonists, our knowledge of factors that facilitate dengue virus infection is limited. Previous dengue virus infection-responsive transcriptome analyses have revealed an increased mRNA abundance of members of the myeloid differentiation 2-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 43 publications
6
72
1
1
Order By: Relevance
“…Here we confirm, for the first time, a role for SCP2 as a DENV host factor in vivo . Taken together with our transcriptomic data, which revealed regulation of lipid transport processes in both transgenic lines, and with previous studies [41,42], these results emphasize important roles for lipid homeostasis during DENV infection in Ae . aegypti .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Here we confirm, for the first time, a role for SCP2 as a DENV host factor in vivo . Taken together with our transcriptomic data, which revealed regulation of lipid transport processes in both transgenic lines, and with previous studies [41,42], these results emphasize important roles for lipid homeostasis during DENV infection in Ae . aegypti .…”
Section: Discussionsupporting
confidence: 90%
“…JAK/STAT activation resulted in the broad induction of numerous transcripts encoding immune recognition and effector molecules, including several that have previously been shown to restrict DENV. In addition, functional pathway analyses revealed that digestion- and lipid transport-related transcripts were differentially regulated in transgenic mosquitoes; these processes have previously been shown to impact DENV replication [41,42,57]. Finally, JAK/STAT activation also down-regulated transcript abundances of several genes that have known or potential roles as DENV host factors.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…NPC2 also plays an important role in dengue resistance of Ae. aegypti mosquitoes and may play a role in a variety of infection systems (Jupatanakul et al ., 2013). A2MRAP (ASTE011001/AGAP003521) is a protein associated with the receptor for alpha-2-macroglobulins.…”
Section: Resultsmentioning
confidence: 99%
“…A number of bacterial species isolated from the mosquito midguts have also been utilized for manipulating their midgut microbiota (paratransgenesis), to modulate the vector competency of the mosquitoes, as a potent strategy for vector management [13–15]. Interestingly, the midgut microbial flora is dynamic and the diversity changes with the development of the vectors, in addition to other factors such as species, sex, life-stage, feeding behavior and geographical origin [1622]. As a conventional assumption, midgut bacterial population is thought to be acquired from the environment, in which the said species develops.…”
Section: Introductionmentioning
confidence: 99%